Pesantrenpreneurship: Strategy for Economic Empowerment of Ma'had Islamic University Students in Indonesia - Nandi Supriyanto; Achmad Chomsun Roziqin; Nanang Zakaria; Masruri; Muhammad Faisal (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Researchers believe that the Pesantreprenuer concept which has been successfully implemented in Islamic boarding schools, especially the Sidogiri Islamic Boarding School, can also be applied in Ma'had in order to improve the economy of Ma'had which can also increase the empowerment of students living in Ma'had. This research is qualitative research with a descriptive approach, namely regarding the concept of Pesantrenprenuership which is applied at the Islamic University of Ma'had to increase the economic empowerment of students living in Ma'had. The data in this research uses secondary data originating from websites, scientific articles, books and other credible references. The result in this article show 1. Ma'had aims to guarantee quality so that students/college students who live at Ma'had can improve their theoretical and practical skills so that they can talk a lot when they go out to the community, 2. Ma'had and Islamic boarding schools have similarities like twins, especially regarding the characteristics of the students/mahasantri who stay together, the learning curriculum, and learning objectives/quality assurance. 3. The Islamic boarding school concept applied in Islamic boarding schools aims to create independent financing for Islamic boarding schools, improve students' skills, and increase students' economic empowerment. 4. The concept of Islamic boarding school is easier to apply in Ma'had because of emotional maturity, intellectual maturity and level of creativity. So that the economic empowerment of mahasantri is easier to achieve in ma'had.